The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1104/pp.93.1.77
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Freezing Tolerance of Root-Tip Cells and Cold Stability of Microtubules in Rye (Secale cereale L. cv Puma)

Abstract: The response of cortical microtubules to low temperature and freezing was assessed for root tips of cold-acclimated and nonacclimated winter rye (Secale cerea/e L. cv Puma) seedlings using indirect immunofluorescence microscopy with antitubulin antibodies. Roots cooled to 0 or -30C were fixed for immunofluorescence microscopy at these temperatures or after an additional hour at 40C. Typical arrays of cortical microtubules were present in root-tip cells of seedlings exposed to the cold-acclimation treatment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
1

Year Published

1991
1991
2000
2000

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 13 publications
3
37
1
Order By: Relevance
“…Our results are not inconsistent with the change in LT5o from -9°to -3°C in root-tip cells of rye following taxol treatment (10). Based on the rye study the suggestion was made that microtubule depolymerization during freezing may be necessary if the tissue is to survive to its normal LT5o (10).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Our results are not inconsistent with the change in LT5o from -9°to -3°C in root-tip cells of rye following taxol treatment (10). Based on the rye study the suggestion was made that microtubule depolymerization during freezing may be necessary if the tissue is to survive to its normal LT5o (10).…”
Section: Discussionsupporting
confidence: 55%
“…Taxol, a taxane alkaloid derived from the western yew, Taxis brevifolia (16), stabilizes microtubules at sub-stoichiometric concentrations relative to tubulin concentration. It stabilizes microtubules in the mitotic spindle (2,9) and cytoplasm (12), in root-tip cells of rye (10), and stabilizes in vitro microtubules from several species (5,13). The finding that root-tip cells of rye containing taxol-stabilized microtubules are less freezing-tolerant than are non-taxol-treated controls (10) suggests that microtubule depolymerization during freezing may have important consequences.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…The higher accumulation of an ABP in the tolerant species may be related to their capacity to modulate the intracellular actin structure needed to develop higher freezing tolerance. It has been reported that low temperature causes microtubule depolymerization in winter rye root tips [2]. The level of depolymerization was related to the degree of freezing tolerance.…”
Section: Amentioning
confidence: 92%
“…These modifications are associated with a reduction in cell water content, increase in intracellular solutes, reduction in cell volume, and an increase in plant erectness [1]. It has been reported that low temperature causes microtubule depolymerization in winter rye root tips [2]. The level of depolymerization was related to the degree of freezing tolerance, suggesting that microtubule depolymerization is important for achieving maximal freezing tolerance.…”
Section: Introductionmentioning
confidence: 99%